The UNDP Accelerator Labs enter a year of maturity: let a thousand flo wers bloom! - Annual report 2022 - labs, UNDP (UNDP, 2022)
The UNDP Accelerator Labs were designed as an agile and dynamic Networ k to allow communication and information transfer between 91 Accelerat or Labs in 115 countries, and with the global innovation ecosystem, UN DP as a whole, and thousands of partners including grassroots innovato rs and their communities. The accumulated knowledge of this Network cr eates new pathways to the solutions that hold the key to sustainable d evelopment problems. What it looked like and how it unfolded last year will be illuminated in this annual report: The UNDP Accelerator Labs enter a year of maturity: let a thousand flowers bloom!